PENGARUH KOMPETENSI, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. DELTA SATRIA DEWATA DENPASAR - Kadek Alan Pranata; Nengah Landra; Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
The purpose of this study was to determine the effect of competence (1), work motivation (2), and work discipline (3) on employee performance PT. Delta Satria Dewata Denpasar is one of the companies engaged in distributing products to several supermarkets and mini marts spread across Bali. This company was founded in 1991. PT. Delta Satria Dewata distributes products ranging from Johnson brand, L'Oréal cosmetics, Arnotts Biscuits, Kraft, Pocari Sweat and several other big products. Delta Satria Dewata strives to improve the quality of its performance, both in providing quality services and by providing quality work on time and meeting targets. From the results of interviews with 10 employees obtained information that (1) lack of competence which includes aspects of knowledge, skills, and work attitudes in accordance with the expected standardization. (2) Lack of motivation provided by the company so that employees tend to be lazy to do work. Finally, (3) the lack of employee discipline which causes tasks that should be completed faster to be delayed and even increased. The sample in this study were 91 samples taken in this study using a saturated sampling technique. This study uses multiple linear regression analysis. The results of this study prove that (1) competence has a positive and significant effect on employee performance. (2) motivation has a positive and significant effect on employee performance. (3) Work discipline has a positive and significant effect on employee performance.